Synthesis of Multiscale Ultrafine Copper Powder via Radio Frequency Induction Coupled Plasma Treatment - Haibo Wu; Wei Zhang; Shenghan Gao; Tiejun Li; Bin Liu (Metals, 2022)
Nano-sized spherical copper powder has important applications in the fields of microelectronic devices, highly efficient catalysts and lubricant additives. In this study, nano-sized and micron-sized spherical copper powders were simultaneously prepared by radio frequency (RF) induction coupled plasma technology. The effects of processing parameters on the powder properties were studied. The results show that by inputting copper powder with D50 = 34.6 μm, nano-sized spherical powder with a particle size of 10–220 nm and micron-sized spherical powder with a particle size of 4.0–144.0 μm were obtained. The ratio of the nano-sized powder reached 86.4 wt.%. The optimal processing parameters are as follows: powder feed rate is 5.5 g/min, carrier gas flow rate is 5–6 L/min and reaction chamber pressure is 15 Psia. When the carrier gas flow rate is 6 L/min, in the plasma zone (>10,000 K), the powder with particle size <42.0 μm is completely vaporized, which forms nano-sized powder during cooling, while the powder with particle size >42.0 μm is melted and partially vaporized, forming a micron-sized powder. The research results provide a new way for engineering the production of copper nano-powder and some other nano-powders with low melting points, such as silver powder, tin powder and so on.